Pdots, a new type of nanoparticle, bind to mTHPC via their lipid modified surface and exhibit very high FRET efficiency between the core and the sensitizer. Issue 17 (7th May 2015) - Haupt, Sara; Lazar, Itay; Weitman, Hana; Senge, Mathias O.; Ehrenberg, Benjamin
<x xml:space="preserve">Abstract</x> Pdots are a new type of nanoparticle which exhibit strong potential for future applications in biophysics and cell biology.